Design and Usability Evaluation of an Android-Based Point of Sales Application Using Goal-Directed Design - Ridho Taufiq Subagio; Ahmad Alif Fauzan; Mohammad Rafi`; Bintang Trilanang Ramadhan; Ade Surachman (APIC, 2026)
The implementation of Point of Sales (POS) systems in culinary MSMEs still faces a major problem in the form of low usability levels of available applications, thus hampering technology adoption in daily operations. This study aims to design and implement an Android-based POS application with a Goal-Directed Design (GDD) approach to improve ease of use and system effectiveness. The case study was conducted on a typical Cirebon culinary MSME, namely the Empal Gentong Mang Sumedi Restaurant. The research method includes Goal-Directed Design stages that include persona identification, user goal formulation, usage scenario design, and application implementation using the Flutter framework . System evaluation was carried out through functionality testing and usability testing using the System Usability Scale (SUS) on 20 respondents using observation, interviews, and questionnaires. The results showed that the developed POS application obtained an average SUS score of 77.25 which is in the Good and Acceptable Usability categories . The relatively homogeneous distribution of scores and the 95% Confidence Interval values which are all above the usability threshold indicate the consistency of user perceptions of the ease of use of the system. These findings indicate that the implementation of Goal-Directed Design contributes significantly to improving the quality of the interface and user experience in Android-based POS applications for culinary MSMEs.